"You Cannot Cure It, Just Control It": Jamaican Adolescents Living With Diabetes. Issue 2 (3rd April 2019) - Anderson, Moji; Tulloch-Reid, Marshall K.
ABSTRACT: Although adolescence is considered a difficult time for diabetes management, there is little published qualitative research on adolescent Jamaicans with diabetes. This study investigates the experiences of Jamaican adolescents living with diabetes to determine how their needs can be addressed. Nineteen adolescents participated in two urban and two rural focus groups and were asked to draw pictures representing their experiences. Thematic analysis was used to analyze their narratives, while their drawings were analyzed using a variation of Lauritsen and Mathiasen's (2003) method. Results show that control was the central theme: children felt controlled by diabetes and the people in their lives. Diabetes restricted their activities and imposed a sense of difference. Support from those around them could be both helpful and constricting. Children tried to resist control through disregarding the rules, being secretive, defiant, and manipulating others into allowing nonadherence. They also tried to adhere to the rules, find a balance between following them and engaging in desired activities, and to be positive. Those most positive about living with diabetes did not feel controlled by diabetes or others' understandings of it and, with loved ones' support, had rejected diabetes' negative meanings. Extreme distress was felt by rural children. All children had been noncompliant. Healthcare practitioners and policymakers should provide education in schools to facilitate fair and effective treatment. Mental health specialists should assist children to negotiate stigma and distress. Group sessions with significant others are important for collaborative decisions on enabling support.